Integrating AI and Generative AI Literacy in English Teacher Education for Young Learners - Dini Utami; Tedi Rohadi (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2026)
AI and Generative AI (GAI) technologies are increasingly shaping education, making their integration into English teacher education essential for preparing pre-service teachers to engage effectively with young learners in digital contexts. This qualitative study examines the integration of AI and GAI literacy inside English teacher education programs at Islamic higher education institutions in Indonesia, specifically on the teaching of English to young learners. Two research questions guide this research: (1) How is AI and Generative AI literacy being integrated into English teacher education programs for young learners in the digital age? and (2) What pedagogical strategies and digital tools are currently used to incorporate AI and GAI into pre-service English teacher education? Data were collected through questionnaires and interviews involving one lecturer and twenty-five pre-service English teachers (PSTs) and were analysed thematically using the Technological Pedagogical Content Knowledge (TPACK) framework. The findings show that AI and GAI literacy is present but implicitly integrated, with AI use driven mainly by student initiative rather than explicit curricular design. Project-based learning served as the main strategy enabling AI use. Pre-service teachers used ChatGPT for lesson planning, Canva for material design, and Quizizz for assessment, while lecturers mainly used assistive tools such as Grammarly and Canva. These practices indicate emerging technological competence but limited pedagogical and ethical structuring of AI use. The study highlights the need for curriculum-level integration of AI literacy to support ethical, pedagogically grounded, and developmentally appropriate TEYL practices.